Amphipathic Binder Integrating Ultrathin and Highly Ion‐Conductive Sulfide Membrane for Cell‐Level High‐Energy‐Density All‐Solid‐State Batteries. Issue 52 (15th October 2021) - Cao, Daxian; Li, Qiang; Sun, Xiao; Wang, Ying; Zhao, Xianhui; Cakmak, Ercan; Liang, Wentao; Anderson, Alexander; Ozcan, Soydan; Zhu, Hongli
Abstract: Current sulfide solid‐state electrolyte (SE) membranes utilized in all‐solid‐state lithium batteries (ASLBs) have a high thickness (0.5–1.0 mm) and low ion conductance (<25 mS), which limit the cell‐level energy and power densities. Based on ethyl cellulose's unique amphipathic molecular structure, superior thermal stability, and excellent binding capability, this work fabricates a freestanding SE membrane with an ultralow thickness of 47 µm. With ethyl cellulose as an effective disperser and a binder, the Li6 PS5 Cl is uniformly dispersed in toluene and possesses superior film formability. In addition, an ultralow areal resistance of 4.32 Ω cm −2 and a remarkable ion conductance of 291 mS (one order higher than the state‐of‐the‐art sulfide SE membrane) are achieved. The ASLBs assembled with this SE membrane deliver cell‐level high gravimetric and volumetric energy densities of 175 Wh kg −1 and 675 Wh L −1, individually. Abstract : Utilizing amphipathic ethyl cellulose as a binder, this work fabricates a thin sulfide solid‐state membrane with an ionic conductivity of 1.65 mS cm −1 and an areal resistance of 4.32 Ω cm 2 . The all‐solid‐state lithium batteries deliver energy densities of 325 Wh kg −1 and 861 Wh L −1 based on the cathode and solid‐state‐electrolyte, and cell‐level energy densities of 175 Wh kg −1 and 670 Wh L −1 .